Talent management: features and benefits for the organisation in the conditions of digitalisation - V. V. Krivopuskov; M. F. Aliev (Цифровая социология)
Today, high-performance employees who are capable of rapid learning, have developed adaptability skills to environmental changes and specific competencies, the so-called “talents”, are of particular value to organisations. Such employees represent a strategic asset of the company and can help in the implementation of various business strategies. The talented employee management system allows to identify, develop, and retain such specialists, which in turn helps to reduce staff turnover and improve the efficiency of the team. The introduction of talented employee management is especially important in the context of digital transformation of the economy as it allows to use all the advantages of digital technologies to achieve corporate goals Also, talent management is not an easy task, and its implementation may require significant efforts and resources. Despite the fact that this process is associated with certain difficulties, such as search and selection of talented specialists in highly competitive conditions, its advantages significantly outweigh the possible risks. It is important to understand that talent management requires constant monitoring and adaptation to changing conditions. This paper describes the features of the talent management system and the advantages of its implementation for an organisation in the context of digital transformation of society.